EFFECT OF OMEGA3+VITAMIN E ON EXPERIMENTAL INFECTION OF LABORATORY MICE WITH PSEUDOMONAS AERUGINOSA AND KLEBSIELLA PNEUMONIAE - May A. Hameed (Basrah Journal of Veterinary Research)
In present study, 40 adult male mice were used and divided into 5 equal groups of 8 mice each. The first group was the control group, in which the mice were fed with standard ration along the period of experiment; the second and third groups were fed on fats free ration for 14 days while the fourth and fifth groups were fed on Omega3+Vitamin E supplemented ration for 14 days too. The test organisms were suspended in phosphate buffer solution (PBS) and 10-folds serial dilutions were done for (CFU) count. Then, the animals of the second and fourth groups were injected intramuscularly with 22×105 (CFU) of Pseudomonas aeruginosa bacteria, while the animals of the third and fifth groups were injected intramuscularly with 18×106 (CFU) of Klebsiella pneumoniae bacteria. After 24 hours all mice of the third group and 3 mice of the fifth group died; their thigh muscles, livers, lungs, spleens and stomachs were taken, weighed and homogenized with phosphate buffer solution (PBS) to count the (CFU) in these organs. 2 days later, the remainder 5 mice of the fifth group were euthanized and the previous processes were done. For the second and fourth groups, after 48 hours of the bacterial injection all mice of the second group and 4 mice of the fourth group died, the previous processes were done for the bacterial count. 2 days later the remainder 4 mice of the fourth group were euthanized for the bacterial count purpose. The results revealed that the use of Omega3+Vitamin E as a supplements to ration increased the survival of mice and the organs bacterial count of the Omega3+Vitamin E fed mice decreased significantly as compared to those of the fats free fed animals at (P≤0.05).